PENDIDIKAN RESOSIAL: RESOLUSI TERHADAP DILEMA MASYARAKAT MODERN ABAD 21 YANG TERALIENASI - Laely, Titi Anisatul (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2016)
Technology has been spread until education scope. however, many people are getting technology addict. this caused the society got disturbance to communicate and unabel to express their urge and sense, so that the relation with other people will be hampered, not only with the human but also with the nature and also the God. It makes many deviate behaviors, such as: nature destroy, criminal, and immoral. this is the consequences of the modern society who is allianated. in this 21 st century, we must have a sollution. in this case, Resocial education whic is based on the nation cultural context is able to become alternative sollution toward this case.Resocial education is able to give education paradigm which is more credibleand able to help to form the religious, social and good character. it willdeveloping the nation next generation who has a high intelectual abillitywhic is based by religious intelectual, have a good personality and creativitywhich is gotten from the nature.